Sembilan Fungsi Saluran Distribusi: Kunci Pelaksanaan Kegiatan Distribusi yang Efektif - Henky Lisan Suwarno (Jurnal Manajemen Maranatha, 2006)
A marketing channel performs the work of moving goods from producers to consumers. It overcomes the time, place and possession gaps that separate goods and service from those who need or want them. Members of the marketing channel perform a number of key functions: information, promotion, negotiation, ordering, finance, risk taking, physical, payment and title. The study of nine marketing channel functions is to give lesson about the importance members of marketing channel to concern the nine marketing channel functions as the key of effectiveness marketing channel